Brucella abortus lipopolysaccharide in murine peritoneal macrophages acts as a down-regulator of T cell activation - Forestier, Claire (2000)
Macrophages play a central role in host immune responses against pathogens by acting as both professional phagocytic cells and as fully competent APCs. We report here that the LPS from the facultative intracellular Gram-negative bacteria Brucella abortus interferes with the MHC class II Ag presentation pathway. LPS inhibits the capacity of macrophages to present hen egg lysozyme (HEL) antigenic peptides to specific CD41 T cells but not those of OVA to specific CD81 T cells. This defect was neither related to a decrease of MHC class II surface expression nor to a deficient uptake or processing of HEL. In addition, B. abortus LPS did not prevent the formation of SDS-resistant MHC class II complexes induced by HEL peptides. At the cell surface of macrophages, we observed the presence of LPS macrodomains highly enriched in MHC class II molecules, which may be responsible for the significant down-regulation of CD41 T cell activation. This phenomenon may account for the avoidance of the immune system by certain bacterial pathogens and may explain the immunosuppression observed in individuals with chronic brucellosis. The Journal of Immunology, 2000, 165: 5202–5210.